Fungal and other spore counts as predictors of admissions for asthma in the Trent region. Issue 11 (1st November 2000) - Newson, R; Strachan, D; Corden, J; Millington, W
Abstract : OBJECTIVES: The importance of airborne fungal and other spores in provoking asthma attacks is uncertain. Panel studies have generated evidence that suggests a link between outdoor spore counts and severity of asthma. There have been no population based time series studies relating outdoor exposure to spores with incidence of attacks of asthma. METHODS: Outcomes were hospital admissions for asthma on 2002 days during 1987–94, for children and adults in the Trent region of England. Predictors were daily counts of 25 spore taxa from volumetric traps in Derby on the same and previous day. Admissions for asthma were adjusted for weekly, seasonal, and longer term trends by log linear autoregressive models. Spore counts on 6 days of asthma epidemics were also examined. RESULTS: When spore counts for individual taxa were analysed as quantitative variables, two positive and two negative correlations (out of a possible 100) were significant at the 5% level. When spore counts were dichotomised at the 90th percentile, one negative and eight positive correlations (out of 100) were significant at the 5% level. All significantly positive associations related to admissions among children, but none involved the total spore count. However, total spores were above the 90th percentile on four of the six epidemic days (odds ratio (OR) 9.92, 95% confidence interval (95% CI) 1.41 to 109.84), but epidemics occurred on only four of 343 days with high total moulds. CONCLUSIONS: There was some evidence that exceptional rates of admission for asthma tend to occur on days with high total mould spore counts, but no specific taxon was consistently implicated. The predictive power was insufficient to support a public warning system.